A legitimidade democrática do Supremo Tribunal Federal: contribuições para a prática do ativismo judicial - Maia, Vinícius Lins [UNESP] (2014)
We discuss the possibility of improving the democratic legitimacy of the Supreme Court, aiming to better settle its Judicial Activism with the premises of the Democratic State of Law. It is observed that the phenomenon of Activism, despite of the critics, occurs in contemporary western societies, so that a discussion that pursues means to democratically legitimize the exercise of judicial proactive is demanded. For this, we will present manners to densify the legitimacy of the Supreme Court, on the prospect of objective legitimacy and exercise. Regarding the objective legitimacy, it is understood that the realization of Fundamental Rights is an instrument of its improvement; thus, the Judicial Activism the more it is committed to the realization of these rights the more it is justified. Regarding the legitimacy of the exercise, its democratization will occur through the inclusion of social parties interested in decision making. For this reason, we analyze the mechanism of amicus curiae participation and its actual ability to pluralize the debate, examining to what extent the use of such instruments in the manner as it is currently done makes it able to influence the dynamics of the decision-making process. Therefore, under these two aspects of densification - the objective legitimacy and exercise - it is believed that the Supreme Court would remain as an important arena for the realization of fundamental rights, however, best conformed to the democratic principle